An immunoassay for the measurement of (1→3)-β-D-glucans in the indoor environment - Douwes, Jeroen (Hindawi Publishing Corporation, 1997)
An inhibition enzyme immunoassay was developed for quantitation of (1→3)-β-D-glucans in the indoor environment. Immunospecific rabbit antibodies were produced by immunization with bovine serum albuminconjugated laminarin.The laminarin calibration curve ranged from 40 to 3000 ng/ml.Another (1→3)-β-D-glucan (curdlan) showed a similar inhibition curve, but was less reactive on a weight basis. Pustulan, presumed to be (1→3)-β-D-glucan, also showed immunoreactivity in the assay. Control experiments indicated that this was due to (1→3)-β-D-glucan structures. Other non-(1→3)-β-D-glucan polysaccharides did not react. (1→3)-β-Dglucan was detectable in dust from a variety of occupational and environmental settings. We conclude that the new assay offers a useful method for indoor (1→3)-β-Dglucan exposure assessment.